2021
DOI: 10.1088/1361-6528/ac23f9
|View full text |Cite
|
Sign up to set email alerts
|

C60-encapsulated TiO2 nanoparticles for selective and ultrahigh sensitive detection of formaldehyde

Abstract: The current study concerns development of fullerene-C 60 -encapsulated TiO 2 nanoparticles hybrid for an efficient detection of volatile organic compounds (VOCs). The nanocomposite was synthesized via chemical route by using hydrated fullerene-C 60 and sol-gel derived undoped ptype TiO 2 nanoparticles. The nanocomposite was characterized morphologically and structurally comparing with pure C 60 clusters and pure TiO 2 nanoparticles as the reference materials. The average diameter of the C 60 -encapsulated TiO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Table compares the sensing performances to HCHO between this work and recent studies on the TiO 2 - or In 2 O 3 -based sensor reported in the literature. Hollow In 2 O 3 /TiO 2 nanocomposites developed herein have a better overall performance with a higher response, a lower operating temperature (RT), a better detection limit, and shorter response/recovery times. ,,, …”
Section: Resultsmentioning
confidence: 99%
“…Table compares the sensing performances to HCHO between this work and recent studies on the TiO 2 - or In 2 O 3 -based sensor reported in the literature. Hollow In 2 O 3 /TiO 2 nanocomposites developed herein have a better overall performance with a higher response, a lower operating temperature (RT), a better detection limit, and shorter response/recovery times. ,,, …”
Section: Resultsmentioning
confidence: 99%
“…In figures 7(a)-(d), all the sensors responded in a positive direction of the y-axis unfolding the p-type semiconducting behavior of the SrTiO 3 nanostructures [24]. The p-type conductivity of the SrTiO 3 nanoforms possibly originated from the p-TiO 2 nanoparticles used in hydrothermal synthesis [29]. The higher concentration of Ti vacancy (Ti +4 ) compared to the oxygen vacancy is responsible for the p-type behavior of undoped TiO 2 [29,55,56].…”
Section: Sensor Studymentioning
confidence: 95%
“…The p-type conductivity of the SrTiO 3 nanoforms possibly originated from the p-TiO 2 nanoparticles used in hydrothermal synthesis [29]. The higher concentration of Ti vacancy (Ti +4 ) compared to the oxygen vacancy is responsible for the p-type behavior of undoped TiO 2 [29,55,56]. In the transient measurement (figures 7(a)-(d)), ethanol concentration varied from 0.5 to 200 ppm.…”
Section: Sensor Studymentioning
confidence: 99%
See 2 more Smart Citations